2016
DOI: 10.1016/j.ejor.2015.06.078
|View full text |Cite
|
Sign up to set email alerts
|

Recent evidence on the effectiveness of group model building

Abstract: Group model building (GMB) is a participatory approach to using system dynamics in group decision-making and problem structuring. This paper considers the published quantitative evidence base for GMB since the earlier literature review by Rouwette et al. (2002), to consider the level of understanding on three basic questions: what does it achieve, when should it be applied, and how should it be applied or improved? There have now been at least 45 such studies since 1987, utilising controlled experiments, field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 85 publications
3
99
0
Order By: Relevance
“…O'Keefe then suggests three particular areas for further research: experiments where the provision of data is varied, experiments that show how the use of models can help users overcome cognitive biases, and experiment with groups engaged in model creation and use. The review by Scott, Cavana and Cameron (2015) goes beyond experimental evidence but only focuses on the case of group model building (GMB). They found that there is some evidence that GMB is more effective at supporting communication and consensus than traditional facilitation in a range of contexts.…”
Section: Introduction To the Articles In The Special Issuementioning
confidence: 99%
“…O'Keefe then suggests three particular areas for further research: experiments where the provision of data is varied, experiments that show how the use of models can help users overcome cognitive biases, and experiment with groups engaged in model creation and use. The review by Scott, Cavana and Cameron (2015) goes beyond experimental evidence but only focuses on the case of group model building (GMB). They found that there is some evidence that GMB is more effective at supporting communication and consensus than traditional facilitation in a range of contexts.…”
Section: Introduction To the Articles In The Special Issuementioning
confidence: 99%
“…Group model building (GMB): GMB is a process of building visual qualitative conceptual models (i.e., causal loop diagrams (CLDs)) and quantitative dynamic models (i.e., SD) jointly with stakeholders [16][17][18]. Different GMB sessions can have different purposes such as identification of a dynamic hypothesis, discussion around the system boundary, examination of potential scenarios of policy implementation, to name a few.…”
Section: Review Of Participatory Sd Modelling Approachesmentioning
confidence: 99%
“…The direct examination of microlevel behaviour allowed us to come to conclusions based on observations of characteristics for which objective measures can be found. This can be seen as complementary to research that-although valuable-hinges on subjective (self) evaluations of decision making support (Rosenhead and Mingers 2001; Rouwette et al 2002;Scott et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies, mainly executed in natural settings, have reported positive outcomes supporting the value of facilitated modelling approaches in these settings (see e.g., Phillips 2007;Rouwette et al 2002;Scott et al 2016). It is difficult, however, to clearly establish the link between context, process and outcomes of decision support (Schilling et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation